2016 IEEE International Conference on Robotics and Automation (ICRA) 2016
DOI: 10.1109/icra.2016.7487320
|View full text |Cite
|
Sign up to set email alerts
|

Model predictive control for dynamic footstep adjustment using the divergent component of motion

Abstract: This paper presents an extension of previous model predictive control (MPC) schemes to the stabilization of the time-varying divergent component of motion (DCM). To address the control authority limitations caused by fixed footholds, the step positions and rotations are treated as control inputs, allowing the generation and execution of stable walking motions, both at high speeds and in the face of disturbances. Rotation approximations are handled by applying a mixedinteger program, which, when combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 22 publications
(53 reference statements)
0
40
0
Order By: Relevance
“…Eqs. (2) and (3) show how the CoM state evolves after time t, from the initial state x(0) x(0) T to the final state x(t) x(t) T ; we use vector x to denote the CoM state x x T .…”
Section: Preliminariesmentioning
confidence: 99%
“…Eqs. (2) and (3) show how the CoM state evolves after time t, from the initial state x(0) x(0) T to the final state x(t) x(t) T ; we use vector x to denote the CoM state x x T .…”
Section: Preliminariesmentioning
confidence: 99%
“…To address the above problem, Krausse et al, [14] suggested a formulation of the CP controller within MPC framework. Using MPC, the 3D extension of the CP called divergence component of motion (DCM) is controlled in [15] for the ajustment of footstep positions and orientations in the presence of disturbance. In [16], a CP based MPC is used for push recovery.…”
Section: A Related Workmentioning
confidence: 99%
“…Unlike in [23], [14], [15], [17] where the reference footsteps were predetermined, in this work, they are formulated as variables such that they can be generated automatically on-line. To that end, let us consider that there are only four (m = 4) footsteps (f 1 , f 2 , f 3 , f 4 ) falling within the receding horizon N (it only eases the computation of the CoM's average velocity in the rest of these developments).…”
Section: Self-generated Capture-point Reference Trajectoriesmentioning
confidence: 99%
“…Moreover, the MPC approach guarantees a certain robustness against perturbations. It is therefore not surprising that it has been adopted in many methods for gait generation; e.g., see [8], [9], [10], [11] for linear MPC and [12], [13] for nonlinear MPC.…”
Section: Introductionmentioning
confidence: 99%